Enhancing English Grammar Mastery through Gamification: The Impact of Scrambled Games on Secondary School Students’ Writing Skills - Ramadhanti, Safhira Fauzia; Pratiwi, Dwiyani (JOLLT Journal of Languages and Language Teaching, 2025)
Grammar mastery is a fundamental component of language proficiency, yet many EFL students struggle with learning grammar through conventional methods, which are often perceived as monotonous and ineffective. Gamification has emerged as a promising instructional strategy to enhance student engagement and learning outcomes. This study investigates the effectiveness of Scrambled Games in improving grammar mastery among 11th-grade students at SMAN 1 Depok, particularly in hortatory exposition writing. A Classroom Action Research (CAR) design was employed, as it allows for iterative implementation and direct observation of students’ progress in a real classroom setting. The study involved 33 students, with data collected through pre-tests, post-tests, and classroom observations. Statistical analysis using paired sample t-tests revealed a significant improvement in student performance, with the mean pre-test score increasing from 61.49 to 73.15 post-intervention (p < 0.05). Monitoring protocol results indicated moderate to high engagement levels, with notable gains in problem-solving, active participation, and grammatical accuracy. The findings suggest that Scrambled Games can serve as an effective alternative to traditional grammar instruction, fostering active learning and student motivation. However, implementation challenges, such as varying proficiency levels and time constraints, highlight the need for differentiated instruction and supplementary digital resources. These results underscore the potential of game-based learning in enhancing EFL instruction, providing educators with a dynamic approach to teaching grammar. Future research should explore long-term effects, digital adaptations, and variations in game design to optimize its impact on language learning.